PENGARUH ZAKAT PRODUKTIF TERHADAP PENDAPATAN USAHA MUSTAHIK DI KABUPATEN BANYUMAS - Harjanto, Faathir Rahman; Ahmad, Abdul Aziz; Bambang, Bambang (Indonesian Journal of Islamic Business and Economics (IJIBE), 2020)
This study aims to analyze the role of productive zakat on mustahik business income in Banyumas regency. The method use in this research is quantitative method. The population used in this study was 131 mustahik with 97respondents who where selected using the Solvin formula method. The data analysis technique used is multiple regression. The result in this study indicate that all variables have effect to mustahik business income. The capital variable and labour has a positive and significant effect while the length of business has a negative and significant effect on business income mustahik. While supervision, credit, zakat funds and labor do not affect on business income mustahik. The Implication of this research is that the government through Baznas must optimize the absortion and distribution of zakat and the need for increased supervision carried out by Baznas to the recepients of productive zakat aid so that the assistance distributed can be right on target.